The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1111/jvim.16803
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of treatment of cats with feline infectious peritonitis using parenterally administered remdesivir, with or without transition to orally administered GS‐441524

Abstract: BackgroundNucleoside analog GS‐441524 is effective in treating cats with feline infectious peritonitis (FIP). Investigation into the use of parent nucleotide analog remdesivir (GS‐5734) is needed.ObjectivesTo assess efficacy and tolerability of remdesivir with or without transition to GS‐441524 in cats with FIP and document clinical and clinicopathologic progression over 6 months.AnimalsTwenty‐eight client‐owned cats with FIP.MethodsCats were prospectively recruited between May 2021 and May 2022. An induction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
55
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(61 citation statements)
references
References 29 publications
5
55
0
1
Order By: Relevance
“…All other cats in both treatment groups have continued to remain in clinical remission of their disease. If it is assumed that this cat experienced a relapse of FIP, the relapse rate in this study (overall 8.3%) is similar to other studies that have a demonstrated relapse rate of 3.5-23% of cats treated with either GS-441524, remdesivir, or a combination of the medications [6,7,11,12].…”
Section: Discussionsupporting
confidence: 86%
“…All other cats in both treatment groups have continued to remain in clinical remission of their disease. If it is assumed that this cat experienced a relapse of FIP, the relapse rate in this study (overall 8.3%) is similar to other studies that have a demonstrated relapse rate of 3.5-23% of cats treated with either GS-441524, remdesivir, or a combination of the medications [6,7,11,12].…”
Section: Discussionsupporting
confidence: 86%
“…Bei 11 Katzen wurde die Therapie verlängert; 3 Katzen wurden aufgrund eines Rückfalls der Symptome erfolgreich erneut therapiert. Auch die Katzen dieser Studie zeigten Reizungen an den Injektionsstellen [ 76 ] .…”
Section: Remdesivirunclassified
“…If untreated, FIP is invariably fatal. Recently, antiviral treatments have been established and demonstrated to be effective [ 1 , 2 , 3 ], although a few side effects have been reported [ 4 , 5 , 6 , 7 ] and very little information is available about possible long-term effects [ 7 , 8 ]. Treatment is recommended where the drugs is legally available [ 3 ], but unfortunately, in the large majority of countries, the drug is not licensed; therefore, treatments are not allowed.…”
Section: Introductionmentioning
confidence: 99%